Предмет: Алгебра,
автор: elinakurbanova743
2) Раскройте скобки и упростите выражение.
a) - 6, 2 + (5, 2 - n) =
6) 1 - (2, 9 - y) =
B) - 3, 3 - (- 3, 3 + b) =
Г) 2, 5 - (c - 2, 5) =
срочно пожалуйста
Ответы
Автор ответа:
1
Объяснение:
надеюсь помогла!
сразу извиняюсь за подчерк
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: bogom
Предмет: Русский язык,
автор: Asya200511
Предмет: Английский язык,
автор: ARISKA2006
Предмет: Обществознание,
автор: nelleka05022006
Предмет: Математика,
автор: Jakontik2009